Relationship Between Nitrogen Phosphorus Potassium Content of Soil and Quality Sidimpuan Snake Fruit Based on Altitude - Ali Sahbana, Takdir; Yusriani Nasution; Rasmita Adelina (International Journal of Natural Science Studies and Development (IJOSS), 2025)
The purpose of this research is to determine the relationship between the content of nitrogen, phosphorus and soil potassium on the quality of Sidimpuan snake fruit fruit based on the height of the location. This research was carried out at two different elevations with low and high location criteria at six points.coordinates such as the sub-districts of Palopat Maria, Sigordang, Lobu Layan, Huta Ginjang, Sibio-bio, and Huraba Village, starting from April to May 2024. Meanwhile, soil analysis was carried out at the Andalas University Padang Lab. The results of this research are that the comparison of altitude with the quality of sidimpuan snake fruit has a significant effect on the percentage of sidimpuan fruit flesh. Meanwhile, the relationship between soil nitrogen, phosphorus, potassium and the quality of Sidimpuan snake fruit based on altitude has a significant effect on the dissolved solids content in the lowlands, and the relationship between soil phosphorus and potassium nitrogen content on observing the percentage of fruit flesh in the highlands and lowlands has no real effect. significantly